2011
DOI: 10.4103/1119-3077.84031
|View full text |Cite
|
Sign up to set email alerts
|

Congenital gangrene of the extremities in a newborn

Abstract: Gangrene of the extremities in the newborn is extremely rare at birth. Less than 100 cases have been reported worldwide. Its etiology is obscure in many cases; however, some factors have been associated with it in the newborn, which include vascular injury and embolism. We report a case of a baby with congenital bilateral lower limb gangrene caused by thromboembolic phenomenon from retroplacental hematoma following abruptio placentae and highlight the challenges of managing such condition in resource-poor sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Peripheral arterial ischemia and necrosis threaten the survival of premature newborns. Earlier studies have reported that peripheral arterial ischemia due to congenital ischemia can occur immediately after birth for reasons such as placental ischemia and is difficult to treat effectively [30]. Thus, it is difficult to conclude that nitroglycerin patches would be effective in treating all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral arterial ischemia and necrosis threaten the survival of premature newborns. Earlier studies have reported that peripheral arterial ischemia due to congenital ischemia can occur immediately after birth for reasons such as placental ischemia and is difficult to treat effectively [30]. Thus, it is difficult to conclude that nitroglycerin patches would be effective in treating all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Medical management alone may not suffice to achieve limb salvage in cases where the level of vessel occlusion is in the proximal limb segment 20 . Of 5 cases of newborn upper-limb ischemia, Armstrong et al reported 1 amputation in a child with brachial artery occlusion and salvage of remaining 4 with finger and hand ischemia 7 .…”
Section: Discussionmentioning
confidence: 99%
“…TE phenomena presenting with established ischemic changes at the time of birth, as in our case, are far rarer. A literature search revealed that only about 32 such cases, known as "intrauterine" or "congenital" gangrene, have been reported [6][7][8][9][10][11][12][13][16][17][18][19][20][21][22][23] , highlighting the rarity of this presentation. The presence of ischemic changes at birth suggests some intrauterine insult to the fetus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations